2006
DOI: 10.1002/jbm.a.31085
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of various growth factors in different demineralized bone matrix preparations

Abstract: Besides autografts, allografts, and synthetic materials, demineralized bone matrix (DBM) is used for bone defect filling and treatment of non-unions. Different DBM formulations are introduced in clinic since years. However, little is known about the presents and quantities of growth factors in DBM. Aim of the present study was the quantification of eight growth factors important for bone healing in three different "off the shelf" DBM formulations, which are already in human use: DBX putty, Grafton DBM putty, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 28 publications
3
93
0
3
Order By: Relevance
“…85,234,399 Th ese joints might thus not be reliably compared in osteochondral defect healing models. In general, the eff ectiveness of DBM depends on numerous variables, including the age of the donor, 347 the tissue bank and the lot, 172,173,450 prolonged heat treatment, 196 the size or shape of the graft particles, 155 the nature of the carrier material, the extent of residual bone mineral content, 459 and the method of sterilization. 171 However, most of these variables are not applicable to the commercially available DBM used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…85,234,399 Th ese joints might thus not be reliably compared in osteochondral defect healing models. In general, the eff ectiveness of DBM depends on numerous variables, including the age of the donor, 347 the tissue bank and the lot, 172,173,450 prolonged heat treatment, 196 the size or shape of the graft particles, 155 the nature of the carrier material, the extent of residual bone mineral content, 459 and the method of sterilization. 171 However, most of these variables are not applicable to the commercially available DBM used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMP-2 was originally isolated as a putative inductive factor in DBP, these results show that rhBMP-2 and DBP do not affect all the Wnt components in the same ways. Because Guanidine HCl/ EDTA extracts of demineralized bone contain BMP-2, BMP-4, BMP-7/OP-1, TGF-b1, IGF-I, and other biologically active proteins, 21,22 we proposed that it was unlikely that a single component could duplicate all of the effects of DBP. 6,10 We reported previously that DBP and BMP-2 regulate common and distinct signaling pathways, that DBP stimulates both Smad pathways, the one responsive to TGF/Activin and the one responsive to BMP, 10 and that DBP evoked early changes in Wnt components.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of cDNA and amplification conditions were optimized for each gene product to reflect the exponential phase of amplification. One microliter of the cDNA solution was used in each PCR (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) cycles at 948C for 1 min, 55 or 608C for 1 min, and 728C for 2 min) with human gene specific primers: bigh3/TGFBI and ID3, 10 WNTs, 11 Cbfa1/Runx2 and Col1A1, 18 and SOX9. 19 …”
Section: Cell Cultures In Collagen Scaffoldsmentioning
confidence: 99%
“…Carrington et al [38] demonstrated that TGF-βs were present in DBM following extraction with EDTA-guanidine hydrochloride, but not guanidine hydrochloride alone. Wildemann et al [35] verified that TGF-β1 was present in all the three commercial DBMs, although it was at a low level. Katz et al [18] found a weak Spearman correlation between the level of TGF-β1 in the DBM of donors' bone and its capacity for bone formation.…”
Section: Composition Analysis Of Bone Protein Extractmentioning
confidence: 95%
“…Wildemann et al [35] demonstrated that DBM, which has been demineralized and sterilized by different processing methods, retained different amounts of insoluble proteins by comparing three commercially available DBMs. However, in those studies, BMP-2 was detected at its highest level in all DBMs tested.…”
Section: Composition Analysis Of Bone Protein Extractmentioning
confidence: 99%